Design and Construction of PDAM Water Use Monitoring Based on Internet of Things (IoT) - Faisal Faisal; Hambali Hambali (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2022)
Water is a natural resource that is very important for life in the world for humans, animals and other living things. In a settlement, there are two ways to provide clean water, namely piped and non-piped systems. The piping system itself is managed by the Regional Drinking Water Company (PDAM), which is a local government company that carries out the service function to produce drinking water and clean water for the community. The current problem occurs in the community and is detrimental to the community itself, namely the manual recording system of water usage meters, often the fees charged by the community are not in accordance with the usage meter used. For this reason, an automatic monitoring of water usage was designed. This tool uses a Waterflow to detect the amount of water consumption which is controlled with NodeMCU Esp8266, later monitoring of usage can be seen on the LCD and Thinger.io as a database. Testing this final project using a measuring cup as a comparison of the real water volume with the volume of the results read by the sensor. The test results of the final project will read the volume of water and the rate for usage fees with an error percentage of 0.3%. The resulting data can be monitored in real time through the thinger.io website and smartphones to make it easier to monitor remotely.